2020
DOI: 10.3389/fpls.2020.00576
|View full text |Cite
|
Sign up to set email alerts
|

EjTFL1 Genes Promote Growth but Inhibit Flower Bud Differentiation in Loquat

Abstract: TERMINAL FLOWER1 (TFL1), a key factor belonging to the phosphatidyl ethanolaminebinding protein (PEBP) family, controls flowering time and inflorescence architecture in some plants. However, the role of TFL1 in loquat remains unknown. In this study, we cloned two TFL1-like genes (EjTFL1-1 and EjTFL1-2) with conserved deduced amino acid sequences from cultivated loquat (Eriobotrya japonica Lindl.). First, we determined that flower bud differentiation occurs at the end of June and early July, and then comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
2
13
1
Order By: Relevance
“…EjTFL1-1 is mainly expressed in roots and leaf buds but is expressed at low levels in shoots, ower buds and owers. EjTFL1-2 is mainly expressed in leaf buds, owers, and fruits and is not expressed in the other tissues [30]. In the present study, MiTFL1 genes showed different expression patterns than those reported above.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…EjTFL1-1 is mainly expressed in roots and leaf buds but is expressed at low levels in shoots, ower buds and owers. EjTFL1-2 is mainly expressed in leaf buds, owers, and fruits and is not expressed in the other tissues [30]. In the present study, MiTFL1 genes showed different expression patterns than those reported above.…”
Section: Discussioncontrasting
confidence: 77%
“…In the present study, four TFL1 genes were obtained from 'SiJiMi' mango, and these were named MiTFL1-1, MiTFL1-2, MiTFL1-3 and MiTFL1-4. Multiple copies of TFL1 homologous genes were also found in other plants, such as two in soybean [29], moso bamboo [13] and loquat [30], three in petunia [31], four in cotton [32] and ve in Hevea brasiliensis [33]. In a previous study, only two TFL1 genes, MiTFL1 and MiTFL1a, were found in another mango variety, 'Alphonso', and these corresponded to MiTFL1-2 and MiTFL1-1 in the present study, respectively [34].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Multiple copies of TFL1 homologous genes are also found in other plants, such as two in soybean [ 30 ], moso bamboo [ 13 ] and loquat [ 31 ], three in petunia [ 32 ], four in cotton [ 33 ] and five in Hevea brasiliensis [ 34 ]. In a previous study, only two TFL1 genes, namely, MiTFL1 and MiTFL1a, were found in another mango variety, ‘ Alphonso ’, corresponding to MiTFL1-2 and MiTFL1-1 , respectively, in the present study [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FBD and the blooming time affect the fruit yield and quality. Although several genes related to flower development in cultivated loquat, such as EjLFY, EjAP1, EjFT, EjSOC, EjTFL1 , and EjAGL17 have been cloned (Esumi et al, 2005; Liu et al, 2013; Reig et al, 2017; Jiang et al, 2019; Jiang et al, 2020; Xia et al, 2020), the mechanism of FBD in loquat remains unclear.…”
Section: Introductionmentioning
confidence: 99%